PALYNOLOGY OF THE LA VETEADA FORMATION (PERMIAN) IN THE SIERRA DE NARVÁEZ, CATAMARCA PROVINCE, ARGENTINA (Ameghiniana, 2011)
Eighty-one species of spores and pollen grains together with algae and fungi remains were recovered from the shallow lacustrine successions of the La Veteada Formation at the Chaschuil river section (27°43?50.5??S/68°01?17.0??W), Sierra de Narvaez, Catamarca Province, Famatina Range, which are herein described and/or illustrated. This palynoflora is composed dominantly by a diverse association of taeniate pollen groups (68%), bisaccate (non-taeniate) pollen grains (24%), with less significant proportions of spores. The studied palynoflora is referred to the upper part of the LW (Lueckisporites-Weylandites) Biozone, thus a Middle Permian (Guadalupian) age is established, mainly based on the presence of Corisaccites alutas Venkatachala and Kar, Lueckisporites angoulensis Jardine, L. nyakapandensis Hart, L. stenotaensis Menendez, L. virkkiae (Potonie and Klaus) Clarke, Lunatisporites variesectus Archangelsky and Gamerro, Staurosaccites cordubensis Archangelsky and Gamerro, Striatoabieites anaverrucosus Archangelsky and Gamerro, Vittatina corrugata Marques-Toigo, V. costabilis Wilson, V. subsaccata Samoilovich, Convolutispora archangelskyi Playford and Dino, Striomonosaccites cicatricosus Archangelsky and Gamerro. Several species are recorded for the first time in Permian strata from Argentina, extending their chronostratigraphic records. Lueckisporites balmei (Tiwari and Vijaya) comb. nov. is proposed. Gondwanic biostratigraphic distribution of selected species recorded in this assemblage is presented in a range-chart. This palynofloral association is composed mainly by allochthonous elements derived from gymnosperms, conifers and pteridosperms, together with rare authochthonous elements related to the local vegetation represented by pteridofites and sphenophyll components. Warm arid and/or semiarid climatic conditions prevailed in the Paganzo Basin during deposition of the La Veteada Formation. Resumen. PALINOLOGÍA DE LA FORMACIÓN LA VETEADA (PÉRMICO) EN LA SIERRA DE NARVÁEZ, PROVINCIA DE CATAMARCA, ARGENTINA. Se describen y/o ilustran ochenta y una especies de esporas, granos de polen, algas y hongos hallados en las sucesiones lacustres someras de la Formación La Veteada, la cual aflora en la margen izquierda del río Chaschuil (27°43?50.5??S/68°01?17.0??W), en la Sierra de Narváez, provincia de Catamarca, Sistema de Famatina, los cuales se describen y/o ilustran en esta contribución. La palinoflora está compuesta en forma dominante por granos de polen bisacados estriados (68%) y no-estriados (24%), con significativa menor proporcion de esporas. La palinoflora estudiada se refiere a la parte superior de la Biozona LW (Lueckisporites-Weylandites), que indica una edad pérmica media (Guadalupiano), en base a la presencia de Corisaccites alutas Venkatachala y Kar, Lueckisporites angoulensis Jardine, L. nyakapandensis Hart, L. stenotaensis Menendez, L. virkkiae (Potonié y Klaus) Clarke, Lunatisporites variesectus Archangelsky y Gamerro, Staurosaccites cordubensis Archangelsky y Gamerro, Striatoabieites anaverrucosus Archangelsky y Gamerro, Vittatina corrugata Marques-Toigo, V. costabilis Wilson, V. subsaccata Samoilocich, Convolutispora archangelskyi Playford y Dino, Striomonosaccites cicatricosus Archangelsky y Gamerro. Varias especies se registran por primera vez en estratos pérmicos argentinos, extendiendo su registro cronoestratigráfico. Se propone la nueva combinación de Lueckisporites balmei (Tiwari y Vijaya) nov. comb. La distribución bioestratigráfica a nivel de Gondwana de especies seleccionadas registradas en esta asociación se presenta en una carta de distribución cronológica. Esta asociación palinológica está compuesta principalmente por elementos alóctonos derivados de gimnospermas, coníferas y pteridospermas, junto con escasos elementos autóctonos relacionados a la vegetación local representados por componentes de pteridofitas y esfenópsidas. Condiciones climáticas cálidas y áridas y/o semiáridas prevalecieron en la Cuenca de Paganzo durante la depositación de la Formación La Veteada.